FOREIGN ECONOMIC COOPERATION AND DEVELOPMENT OF THE REPUBLIC OF KOREA THROUGH THE CONCLUSION OF FREE TRADE AGREEMENTS - Dok Hee OH; Kyung Sook GIL (Eastern European Journal of Regional Studies, 2022)
The article discusses changes in the foreign economic policy of the Republic of Korea in connection with the deterioration of international trade at the beginning of the XXI century. The direct motive for changing the foreign economic policy of the Republic of Korea is the decline in the role of the WTO as a multilateral trading partner. On the other hand, FTA, based on economic cooperation between the two countries, is becoming a new model for economic development and cooperation in the XXI century. Bilateral negotiations are more likely to end than multilateral ones, because they are actively conducted in accordance with the interests of two countries. Therefore, free trade agreements (FTAs) are becoming the main direction of the economic policy of the Korea’s government to adapt foreign economic policy and overcome the negative trend of global economic development. An FTA has various economic effects, such as the development of trade between two countries, improving the efficiency of resource allocation, reviving investment between two countries and stimulating economic growth. In accordance with this situation, the Republic of Korea justifies the relevance of trade and economic cooperation between two countries through the conclusion of an FTA as a means of implementing an active foreign economic policy. The Republic of Korea has become an opportunity to introduce an advanced economic structure through the signing of free trade agreements with advanced countries. On the other hand, it served as an opportunity to strengthen economic cooperation through the signing of free trade agreements with developing countries. For this reason, the experience of the foreign economic policy of the Republic of Korea can serve as a good example for the economic development of developing countries.